Study on the mechanical properties of polyurethane (PU) grouting material of different geometric sizes under uniaxial compression. (30th October 2020) - Li, Manjun; Du, Mingrui; Wang, Fuming; Xue, Binghan; Zhang, Chao; Fang, Hongyuan
Highlights: Micromorphology of the PU grout materials of different densities were analyzed. Uniaxial compression test was conducted on the PU grout materials. Effects of density, size of PU samples on the compressive strength were studied. The preferred geometric size of PU samples for the uniaxial compression test is suggested. Abstract: Polyurethane (PU) is increasingly adopted as grouting materials in the non-excavation rehabilitation of infrastructures. The compressive strength of PU materials is the key to achieving a desirable grouting effect. However, the geometric sizes of PU samples in the uniaxial compression test are not specified yet, which makes the test results less universal. Here, PU samples with a square cross-section were prepared with different densities and geometric sizes. The micromorphology of the PU matrices was investigated via a scanning electron microscope (SEM). Uniaxial compression tests were conducted, and the effects of density, side length ( l ), and height to side length ratio ( H / l ) of the samples on the mechanical properties were analyzed. The results show that micro foams in PU matrices have average equivalent diameters and average eccentricities of 50–116 μm and 0.55–0.78, respectively. When the density increases, the foams become smaller and more sphere-like. Under the uniaxial load, until strain hardening occurs, both the varied density, l and H / l bring little influence on the variation laws of stress with the strain. The mechanical properties of PU grouting materials increase with the increased density following a power function. When l or H / l changes, the mechanical properties of low-density PU (≤0.30 g/cm 3 ) are little affected while those of high-density PU vary significantly but irregularly. The larger PU samples may be weaker than the smaller ones but may also be stronger. Cubic PU samples with a side length of 40 or 50 mm are preferred for the uniaxial compression test.